1988
DOI: 10.1200/jco.1988.6.4.642
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized trial of fluorouracil versus fluorouracil plus cisplatin in the treatment of metastatic colorectal cancer: a Hoosier Oncology Group trial.

Abstract: From May 1984 through December 1986, 141 patients with metastatic adenocarcinoma of the colon or rectum were entered on this Hoosier Oncology Group (HOG) trial evaluating the role of cisplatin in systemic therapy. Patients were stratified by the presence or absence of hepatic metastases and by performance status, and were subsequently randomized to receive fluorouracil (5-FU) (15 mg/kg/wk) alone or the same dose of 5-FU plus cisplatin (60 mg/m2 every 3 weeks). The total duration of treatment was six cycles (18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1

Year Published

1990
1990
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(25 citation statements)
references
References 5 publications
1
23
1
Order By: Relevance
“…However, the effect of cisplatin on colorectal cancer is weak. Loehrer et al (1988) and Grem et al (1993) reported rates of response of colorectal cancer to cisplatin-based chemotherapy of 22 and 19%, respectively. On the other hand, for oxaliplatin-based chemotherapy, de Gramont et al (2000) reported that the response rate was 50%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effect of cisplatin on colorectal cancer is weak. Loehrer et al (1988) and Grem et al (1993) reported rates of response of colorectal cancer to cisplatin-based chemotherapy of 22 and 19%, respectively. On the other hand, for oxaliplatin-based chemotherapy, de Gramont et al (2000) reported that the response rate was 50%.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, its spectrum of activity and mechanisms of action or resistance differ from those of cisplatin (Raymond et al, 2002;Fuertes et al, 2003;Wang and Lippard, 2005). Oxaliplatin is used against colorectal cancers as a key drug in FOLFOX regimens, and its objective response rate for colorectal cancer is superior to that of cisplatin (Loehrer et al, 1988;Grem et al, 1993;de Gramont et al, 2000;Andre et al, 2004). However, the molecular mechanism(s) underlying the clinical results and that reason that oxaliplatin has such a potent anticolorectal cancer effect compared with cisplatin are unclear.…”
mentioning
confidence: 99%
“…Several treatment modalities have been studied consisting of cytostatics alone (Loehrer et al, 1988) or of cytostatics in combination with other agents (Wadler et al, 1989) or with radiotherapy (Boulis Wassif, 1982). Although the use of adjuvants of treatments found effective for advanced disease has been disappointing, recent results appear to confirm the beneficial effects of cytostatics if administered in the immediate postoperative period (Mayer, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Neither study found differences in response and overall survival; one of these trials reported the median duration of remission was superior for uorouracil alone (p ¾ 0.05) (104).…”
Section: Fluorouracil In Combination With Cisplatinmentioning
confidence: 95%